The Role of Actin Cytoskeleton in Dendritic Spines in the Maintenance of Long-Term Memory - Basu, Sreetama; Lamprecht, Raphael (Frontiers in Molecular Neuroscience, 2018)
Evidence indicates that long-term memory formation involves alterations in synaptic efficacy produced by modifications in neural transmission and morphology. However, it is not clear how such alterations induced by learning, that encode memory, are maintained over long period of time (up to a life time) to preserve long-term memory. This is especially intriguing as the half-life of most of the proteins that underlie such changes is usually in the range of hours to days and these proteins may change their location over time. In this review we describe studies that indicate the involvement of dendritic spines in memory formation and its maintenance. These studies show that learning leads to changes in the number and morphology of spines and that disruption of spines morphology and number is associated with impairment in memory maintenance. We further ask how changes in dendritic spines morphology, induced by learning and reputed to encode memory, are maintained to preserve long-term memory. We propose a mechanism, based on studies described in the review, whereby the actin cytoskeleton and its regulatory proteins, involved in the initial alteration in spine morphology induced by learning, are also essential for spine structural stabilization that maintains long-term memory. In this model glutamate receptors and other synaptic receptors (e.g. Eph receptor) activation during learning leads to the creation of new actin cytoskeletal scaffold leading to changes in spines morphology and memory formation. This new actin cytoskeletal scaffold is preserved beyond actin and its regulatory proteins turnover and dynamics by active stabilization of the level and activity of actin regulatory proteins within these memory spines.